Memorias silenciadas en la construcción de los servicios sociales - García Roca, Joaquín (Cuadernos de Trabajo Social, 2006)
This article reviews the history of the formation of the public social service system in Spain and explores some routes not taken: the rights and aspirations to which they gave rise or created expectations, the origin of deinstitutionalization and the loss of social movement and community development. Neoliberal principals and the exalted rise of management, the conquest of professions and social engineering have contributed to silencing a process which can still be recovered. How? The author proposes the idea that social services must be able to produce personal meaning such as the sense of belonging, trust, identify and recognition. They are values which are cultivated in the worlds of life. For that, the user must cease being a mere client in order to become a co-producer of services for people and take on the role of actor in the process. The intervention that takes shape by building social ties, partnership formulas and means of association whose greatest success is based on the exercise of solidarity and human dignity can be the criteria to create behavioral models.